Calorimetric study of water's two glass transitions in the presence of LiCl - Ruiz, Guadalupe N. (2018)
A DSC study of dilute glassy LiCl aqueous solutions in the water-dominated regime provides direct evidence of a glass-to-liquid transition in expanded high density amorphous (eHDA)-type solutions. Similarly, low density amorphous ice (LDA) exhibits a glass transition prior to crystallization to ice Ic. Both glass transition temperatures are independent of the salt concentration, whereas the magnitude of the heat capacity increase differs. By contrast to pure water, the glass transition endpoint for LDA can be accessed in LiCl aqueous solutions above 0.01 mole fraction. Furthermore, we also reveal the endpoint for HDA's glass transition, solving the question on the width of both glass transitions. This suggests that both equilibrated HDL and LDL can be accessed in dilute LiCl solutions, supporting the liquid-liquid transition scenario to understand water's anomalies.